2002
DOI: 10.1051/0004-6361:20020902
|View full text |Cite
|
Sign up to set email alerts
|

On the brightness and velocity structure of solar granulation

Abstract: Abstract.A 45 min time series of two-dimensional spectra has been obtained with the Vacuum Tower Telescope at the Observatorio del Teide in Izaña, Tenerife. Scans over the non-magnetic Fe i 5576 Å line of a quiet granular field at disk center were taken simultaneously with a time series of broad band images. From the spectra intensity and velocity maps have been calculated at different line-depths. From the white light images granular shapes have been computed by means of an automatic image segmentation algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 28 publications
10
30
0
Order By: Relevance
“…1) originates largely in the first 120 km above τ 500 = 1. So, our findings of a change in dynamics and in topology of the velocity field above these layers is in line with the disappearance of the granular intensity structures with height in the photosphere (Espagnet et al 1995;Krieg et al 1999;Berrilli et al 2002;Hirzberger 2002).…”
Section: D Spatial Velocity Power Spectrasupporting
confidence: 88%
See 2 more Smart Citations
“…1) originates largely in the first 120 km above τ 500 = 1. So, our findings of a change in dynamics and in topology of the velocity field above these layers is in line with the disappearance of the granular intensity structures with height in the photosphere (Espagnet et al 1995;Krieg et al 1999;Berrilli et al 2002;Hirzberger 2002).…”
Section: D Spatial Velocity Power Spectrasupporting
confidence: 88%
“…Concerning granular intensity and velocity fluctuations they found that for structures larger than one arcsec the intensity fluctuations vanish rapidly with photospheric height, whereas the flow velocities stay almost constant up to 250 km. In another paper Hirzberger (2002) investigated statistically the intensity and velocity patterns at different photospheric levels. Applying new and innovative concepts from fractal geometry statistics to the analysis of granular patterns he found that the overall granular shapes are significantly elongated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same results, however, were also claimed to be consistent with a completely random and changing flow pattern that does not require any self-organization of the granular flows (Rast 2002). Other studies find that the temporal coherence time of granulation is consistent with a turbulent Kolmogorov spectrum (Hirzberger 2002;Abramenko et al 2001Abramenko et al , 2002, that some recurrently fragmenting granules survive by means of their descendants for more than 3 hr (Müller et al 2001), but that only large granules with size scales of տ2500 km and lifetimes of տ0.5 hr represent reliable tracers of the surface velocity field (Rieutord et al 2001). It was reassuring to hear that supergranulation flows measured in white light could also be recovered by simultaneous measurements in UV with TRACE (Krijger et al 2002).…”
Section: Are Granular Flows Self-organized or Random?mentioning
confidence: 62%
“…However, so far observational results do not support downward motions faster than upflows. Hirzberger (2002) investigated the velocity field of the photosphere and reported almost the same magnitude of 1.5 km/s for both, upflows and downflows. Kostik & Khomenko (2007) used a bisector analysis to extract the height structure of the velocity field from the asymmetric shape of an absorption line and also found that both upward and downward motions have approximately the same amplitude at heights from 0 km to 500 km.…”
Section: Introductionmentioning
confidence: 83%